Prevalence of tandoor smoke exposure in female patients with asthma: A cross-sectional study from the East of Turkey (Annals of Medical Research, 2021)
Aim: The aim of this study was to evaluate the use of cow dung cake (cdc) for heating, cooking and baking in female patients (pts) with asthma.Material and Methods: This cross-sectional study was conducted between January 2016 and 2018. The study included 522 female pts with asthma. Pts were divided into three groups based on using cdc (for heating, cooking and baking). Secondly, the pts who used cdc in tandoor for baking were evaluated and these pts were divided into three groups based on exposure to tandoor smoke [a) currently using, b) previously used, c) never used]. Age, BMI, comorbidity, the place where pts live, educational status, occupation, smoking status, pulmonary functions and complete blood counts of all pts were evaluated. All statistical calculations were performed with SPSS 23.0.Results: 219 (42%) of all pts were using the cdc, 165 (31.7%) pts were using tandoor, 106 (20.4%) pts had previously used tandoor. The pts who exposed to tandoor smoke previously were significantly older and these pts had higher BMIs. The incidence of comorbidities, the place where pts live, occupation and educational status were significantly different between tandoor smoke exposure groups. The pts who were currently using tandoor for baking lived in villages. In all three groups, most of the women were housewives and most of them who were exposed to tandoor smoke were illiterate. Hemoglobin levels of the pts who were exposed to tandoor smoke were higher. The pts who were currently using tandoor for baking had significantly lower MPV and pulmonary function tests such as FEV1, FVC, PEF and FEF 25% levels. Conclusion: The women with asthma who exposed to tandoor smoke are older, overweight, rural housewife people and they have comorbidities. The pulmonary functions and hemoglobin of them may be affected by exposure to tandoor smoke.
Keywords: Female; asthma; biomass; tandoor smoke